Optimal Timing for the Initiation of Pre-Treatment With 300 mg Clopidogrel Before Percutaneous Coronary Intervention - Steinhubl, Steven R.; Berger, Peter B.; Brennan, Danielle M.; Topol, Eric J. (Journal of the American College of Cardiology, 2006)
Optimal Timing for the Initiation of Pre-Treatment With 300 mg Clopidogrel Before Percutaneous Coronary Intervention Steven R. Steinhubl, Peter B. Berger, Danielle M. Brennan, Eric J. Topol, for the CREDO Investigators To determine the optimal timing of a 300-mg clopidogrel loading dose before a percutaneous coronary intervention (PCI), pre-treatment timing data from 1,762 patients in the Clopidogrel for the Reduction of Events During Observation (CREDO) trial were analyzed using linear splines to summarize the effect of time of pre-treatment as a continuous variable. The difference in the 28-day combined end point of death, myocardial infarction, and urgent target vessel revascularization was not significant between placebo- and clopidogrel-pre-treated patients until ≥15 h pre-treatment, with a 58.8% (p = 0.028) relative reduction in the primary end point in patients pre-treated with clopidogrel ≥15 h compared with placebo. This study sought to determine the optimal timing of a 300-mg clopidogrel loading dose before percutaneous coronary intervention (PCI) in patients enrolled in the Clopidogrel for the Reduction of Events During Observation (CREDO) trial. A loading dose of clopidogrel before a PCI has become relatively commonplace, although the data supporting this practice are limited and sometimes conflicting. Patients were randomized to receive either 300 mg clopidogrel or a matching placebo administered a minimum of 3 h and a maximum of 24 h before PCI. The primary 28-day combined end point was death, myocardial infarction, or urgent target vessel revascularization. Linear splines were used to summarize the effect of the time of pre-treatment as a continuous variable. A total of 1,762 patients were evaluated. For patients randomized to placebo, there was no relationship between the duration of pre-treatment and the occurrence of the primary end point, whereas longer durations of pre-treatment in patients randomized to clopidogrel were associated with improved outcomes. The event rates diverged maximally at 24 h. The difference in outcomes between placebo and clopidogrel pre-treated patients was not significant until ≥15 h pre-treatment, with a 58.8% (p = 0.028) reduction in the primary end point in patients pre-treated with clopidogrel ≥15 h compared with placebo. When a 300-mg loading dose of clopidogrel is used, little benefit is obtained compared with just 75 mg at the time of the PCI when the treatment duration is <12 h. In patients pre-treated for longer durations, the optimal duration seems to approach 24 h.